The bone witch - Chupeco, Rin (2017)
Tea's gift for death magic means that she is a bone witch, a title that makes her feared and ostracized by her community, but when an older bone witch trains her to become an asha--one who can wield elemental magic--Tea will have to overcome her obstacles and make a powerful choice in the face of danger as dark forces approach.
Keywords: Magic -- Fiction; Witches -- Fiction; Fantasy